COSMOLOGY IN ISLAM, CONSTRUCTING ISLAMIZATION OF NATURE SCIENCE - Muhammad Fiqih Cholidi; Safiya Fadlulah (Jurnal Al-Dustur, 2022)
Cosmology is one of the philosophical and scientific objects that become attention in Greek philosophers, especially Aristotle. However, with the times, this cosmology was found in The Qur’an, exactly in the concept of the sky and earth creation which was written and explained by the creator Himself. Then, Islamic scholars and philosophers come up with this issue and choose it as a medium in constructing Islamic science or Islamization of Nature Knowledge that faces fundamental basic deconstruction, so it causes the epistemological flaw in modern science’s body. Seyyed Hossein Nasr, as the inspirator for sacred science, popularize cosmology as one of Islamic science based on him. Past Muslim scholar, Al-Farabi, involved cosmology in integrating Islam and knowledge before. The interesting thing that will be solved in this article is how Muslim scientist, Fakhruddin Ar-Razi interprets creation signs as the source of cosmology in Islam, which leads this toward signs for thinkers. Not only, these cosmology concepts derived from contemporary Muslim scholars and philosophers will also explain the wisdom behind the creation of nature from its microcosmic and macrocosmic not only for increasing people’s faith nor sign but one of the main concepts of Islamization Nature Knowledge, because it is derived from main Muslim guidance, namely The Qur’an Al-Karim.